2003
DOI: 10.1093/ndt/gfg016
|View full text |Cite
|
Sign up to set email alerts
|

Novel truncating mutations in the ClC-5 chloride channel gene in patients with Dent's disease

Abstract: Our study is the first to characterize mutations in the CLCN5 gene in Spanish patients with Dent's disease and expands the spectrum of CLCN5 mutations associated with this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Three of these mutations were novel and consisted of a donor splice site mutation, a deletion-insertion that resulted in a frameshift and an in-frame 3-bp deletion. The remaining mutations consisted of two missense (Ser244Leu and Arg516Trp) and two nonsense (Arg347Stop and Arg718Stop) mutations that have previously been reported in other unrelated patients with Dent’s disease [3, 6, 23]. All of these CLCN5 mutations were confirmed by either restriction endonuclease analysis (fig.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Three of these mutations were novel and consisted of a donor splice site mutation, a deletion-insertion that resulted in a frameshift and an in-frame 3-bp deletion. The remaining mutations consisted of two missense (Ser244Leu and Arg516Trp) and two nonsense (Arg347Stop and Arg718Stop) mutations that have previously been reported in other unrelated patients with Dent’s disease [3, 6, 23]. All of these CLCN5 mutations were confirmed by either restriction endonuclease analysis (fig.…”
Section: Resultsmentioning
confidence: 64%
“…1), the in-frame deletion (523delVal) and the donor splice site mutation (fig. 2) represent novel CLCN5 mutations, whereas the missense (Ser244Leu and Arg516Trp) and nonsense mutations (Arg347Stop and Arg718Stop) occur in other unrelated patients with Dent’s disease [3,4,5,6, 23, 27,32,33,34,35,36,37]. The total number of CLCN5 mutations now published, including the results of our present study, is 148, and these are scattered throughout the coding region, with no evidence for major mutational hot spots [27, 28, 34,37,38,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Different types of disease-causing mutations in the CLCN5 gene have been reported (Lloyd et al 1996;Hoopes et al 1998;Morimoto et al 1998;Yamamoto et al 2000;Carballo-Trujillo et al 2003;ClaverieMartin et al 2003;Ludwig et al 2005). Most of these mutations are single nucleotide substitutions that are scattered throughout the coding sequence of the gene.…”
Section: Introductionmentioning
confidence: 99%
“…Dent's disease is a renal tubular disorder characterized by low-molecular-weight proteinuria, hypercalciuria, nephrocalcinosis, nephrolithiasis, rickets, and eventual renal failure (OMIM: 300009; Lloyd et al 1996). This disease is caused by mutations in the CLCN5 gene that encodes the voltage-gated chloride channel ClC-5 (Fisher et al 1995;Lloyd et al 1996;Carballo-Trujillo et al 2003) although recent findings have shown that mutations in the OCRL1 gene, also involved in proximal tubular function, are responsible for the disease phenotype in some patients (Hoopes et al 2005). Studies with ClC-5 knockout mice showed that loss of ClC-5 function results in an endosomal acidification defect and reduced proximal tubular protein reabsorption, which explain the symptoms of Dent's disease (Piwon et al 2000).…”
Section: Introductionmentioning
confidence: 99%